Case study – Kemess South Mine site reclamation and closure – contaminated sites assessment and remediation (non-core areas) - Cameron, M; North, R; Wilkins, J; Flemming, L (Mine Closure 2011: Sixth International Conference on Mine Closure, 2011)
The Kemess South Mine site is owned and operated by Northgate Minerals Corporation (NMC), and is a large porphyry gold and copper open-pit mine that is scheduled for closure in 2011. Hemmera was engaged to assess non-core areas of the mine site as defined in the British Columbia (BC) Environmental Management Act to facilitate closure. The Kemess South Mine, like most mine sites, is not a typical contaminated site given the remote location relative to populated areas and the scale of the site. Therefore, applying standard BC Contaminated Sites Regulation approaches and guidelines are not only inefficient and more costly than necessary, but potentially unnecessary to achieve the closure objective and regulatory acceptability. Hemmera implemented a risk-based approach to develop an appropriate level of field investigation and data evaluation that would be responsive to the needs of NMC. Hemmera used a conceptual model approach where contaminant sources and the receiving environment were determined prior to conducting investigations. A data gap field investigation was initiated to support a Screening Level Risk Assessment (SLRA). The results of the SLRA risk assessment identified areas requiring risk management (including further investigation, remediation or more detailed risk assessment) or no further action. Using these results Hemmera completed a remedial action plan as part of the overall strategy to successfully address the contaminated sites aspects of the Kemess South Mine site closure plan. Overall the mine site contamination was not considered extensive based on the application of a site specific risk based approach. Consequently, extensive remediation was not required nor recommended in as part of the overall mine site closure plan.